An Analysis of Macro Nutrition in Red Dragon Fruit (Hylocereus Polurhizus) Peel Dodol - Widyawaty; Ayu Lestari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Dragon fruit peel contains high anthocyanin, pectin, and fiber. In addition, it also has an antioxidant capacity, ant proliferative effect, and polyphenols. In addition, the antioxidant activity in the peel of the dragon fruit is greater than in its flesh. The purpose of this study is to analyze the macronutrient of dragon fruit peel dodol. This is experimental research with laboratory analysis. The implementation includes data, analysis, and interpretation of the data obtained from the results of laboratory analysis. The sample of this research is 1-2 kg of dragon fruit peel. Based on the research result, the carbohydrate content in sample 1 test 1 is 3021 mg and test 2 is 3570 mg, in sample 2 test 1 is 3881 and test 2 is 4050 mg. The protein content of sample 1 test 1 is 1023 mg and test 2 is 1264 sample in test 1 of 1183 mg in test II of 1130 mg. The fat content value of sample 1 test 1 is 571 mg and test 2 is 684 mg, sample 2 of test 1 is 663 mg in test 2 is 730 mg. It is suggested that the government should take some food diversification to increase people’s interest to consume nutritious food to increase immune system so that the community’s nutritional status can increase.